Expansão in vitro de células-tronco mesenquimais cultivadas em biorreator de fibra oca - Mizukami, Amanda (Universidade Federal de São Carlos, 2011)
The mesenchymal stem cells (MSCs) are multipotent stem cells that can differentiate into various types of tissue, a characteristic that makes them interesting for applications in cell therapy. Moreover, cells are anchorage-dependent (ability to adhere to surfaces), easy isolation and rapid expansion in vitro. The traditional cultures of anchorage-dependent animal cells, usually grown in monolayers, resulting in low crop yield and cell recovery, preventing the use of MSCs in therapeutic applications. The need for alternative farming techniques for expansion of MSCs in a large scale have led researchers to the use of "bioreactor technology," which has been seconded from the bioreactor, spinner flask with microcarriers and hollow fiber (hollow fiber). The objective of this work was to develop a method of cultivation known as mesenchymal stem cell line hMSC-TERT in spinner flasks with microcarriers for subsequent inoculation into hollow-fiber bioreactor, aiming at the efficient expansion and the subsequent recovery of MSCs so that preserve their differentiation potential in order to be used in cell therapy. In cultured, we used the microcarrier Pronectin ® F 100 mL spinner flasks with culture medium α-MEM with 15% fetal calf serum, kept in a CO2 incubator at 37 ° C and pH between 7.2 and 7.4. In cultures in spinner flasks were adopted strategies such as supplementation of the culture medium, exchanges of culture medium during cultivation, addition of reagents to reduce clusters of microcarriers, to increase productivity for the subsequent cell inoculation in hollow fiber bioreactor. The use of these strategies has increased productivity cell, achieving a best result of cell multiplication factor (MCF) of 5.79. However, obtaining higher FMC was drastically limited by the formation of clusters of microcarriers in a gel matrix.The cell recovery was low maintenance and analysis of the antigenic phenotype by flow cytometry confirmed the conservation of phenotypic characteristics of hMSC-TERT. The hollow fiber bioreactor is an alternative to the clusters of microcarriers, it allows oxygenation and adequate supply of nutrients. Thus, in experiments carried out in hollow-fiber bioreactor used the α-MEM supplemented with 15% FBS (v / v), 2.0 g / L glucose, 2.50 mM glutamine, 2.60 mM arginine, 0.07% antifoam PPG. The cells were inoculated after 48 hours of cultivation in spinner flasks in a gel composed of collagen, hyaluronic acid, agar (1.5%) in the proportion 0.75: 0.037: 0.21 at pH 7.2 to 7.4 . Thus, the resulting gel was mixed with culture medium in α-MEM 1:3 ratio, to provide better grip on the fibers. The total expansion factor, ie the one calculated from the inoculation of the spinner to the end of cultivation in hollow fiber bioreactor was 11, 2, which can be considered the greatest value achieved in this work. It is clear that this expansion factor can still be easily overcome by adopting strategies to grow more frequent replacement of culture medium. This hypothesis is strengthened by the proven fact that the microcarriers are not yet saturated with cells at the end of the experiment.
Keywords: Biotecnologia; Célula animal; Células-tronco mesenquimais; Biorreatores; Biorreator de fibra oca; ENGENHARIAS::ENGENHARIA QUIMICA